TEACHING LISTENING PROCEDURE TEXT BASED ON CONTEXTUAL TEACHING AND LEARNING APPROACH - Noviani, Sasi; ., Ikhsanudin; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research aims at knowing the level of effectiveness the use of CTL Approach in teaching listening procedure text to the ninth grade students of MTs Ushuluddin Sungai Jaga A Bengkayang. The research method used is a Pre Experimental Research. The study sample is 32 students. Based on the analysis of the data, the students’ mean score of effectiveness was 74.75. This score showed a significance difference to the pretest result which was 58.87. Furthermore, the Effect Size computation where the value of ES was 2.56 (categorized as high). It is therefore, the Alternative Hypothesis (Ha) is accepted and Null Hypothesis is rejected and it can be concluded that Contextual Teaching and Learning approach was effective in teaching listening procedure text. Keywords: CTL, Listening, Procedure Text. Abstrak: Penelitian ini bertujuan untuk mengetahui tingkat keefektifpan menggunakan pendekatan CTL didalam pengajaran mendengarkan pada teks procedur untuk siswa kelas IX MTs Ushuluddin Sungai Jaga A Bengkayang. Metode penelitian yang digunakan adalah pre eksperimental. Sampel penelitian adalah 32 siswa. Berdasarkan analisis data, nilai rata-rata siswa efektif adalah 74,75. Nilai ini menunjukan signifikan yang berbeda dengan tes tertulis (pre-tes) yang mana hasilnya 58,87. Selanjutnya, perhitungan ukuran efek (effect size) dimana nilai dari ukuran efek adalah 2,56 (kategori tinggi). Oleh karena itu, alternatif hipotesis adalah diterima dan nol hipotesis adalah ditolak dan bisa di simpulkan bahwa pendekatan Contextual Teaching and Learning adalah efektif didalam pengajaran mendengarkan teks procedur. Kata Kunci: CTL, mendengar, teks procedur